2012
DOI: 10.4161/auto.8.2.18535
|View full text |Cite
|
Sign up to set email alerts
|

Atg5 and Ambra1 differentially modulate neurogenesis in neural stem cells

Abstract: Neuroepithelial cells undergoing differentiation efficiently remodel their cytoskeleton and shape in an energy-consuming process. The capacity of autophagy to recycle cellular components and provide energy could fulfill these requirements, thus supporting differentiation. However, little is known regarding the role of basal autophagy in neural differentiation. Here we report an increase in the expression of the autophagy genes Atg7, Becn1, Ambra1 and LC3 in vivo in the mouse embryonic olfactory bulb (OB) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
114
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 45 publications
9
114
1
Order By: Relevance
“…With regards to the central nervous system, the clinical findings of callosal agenesis, cortical hypoplasia, and cerebellar malformation connect EPG5-dependent autophagy to central nervous system development. Regulators of neuronal autophagy, such as Ambra1 or Atg5, have been found to play a crucial role during early neuronal differentiation 36,37 and postnatal adaptation 38 by assuring that basal autophagy disposes cellular components and provides energy to enable the dynamic changes necessary in the developing brain.…”
Section: Autophagy In Pediatric Brain Diseasesmentioning
confidence: 99%
“…With regards to the central nervous system, the clinical findings of callosal agenesis, cortical hypoplasia, and cerebellar malformation connect EPG5-dependent autophagy to central nervous system development. Regulators of neuronal autophagy, such as Ambra1 or Atg5, have been found to play a crucial role during early neuronal differentiation 36,37 and postnatal adaptation 38 by assuring that basal autophagy disposes cellular components and provides energy to enable the dynamic changes necessary in the developing brain.…”
Section: Autophagy In Pediatric Brain Diseasesmentioning
confidence: 99%
“…3 So far, numerous evidences about the autophagy function have mainly concentrated on nervous system, such as, the differentiation of neuroepithelial cells or the neurodegeneration and behavioral deficits by Atg7 conditional knockout in mouse neurons. 4,5 However, autophagy functions on other types of cells remain controversial and much less was known about the function of Atg7 on the development of embryos. It was reported that mice with targeted mutations Atg7 died within 1 day after birth, and the weight of the Atg7 KO mice was significantly lower than that of normal mice.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, upregulation of autophagy-genes has also been shown during neuronal differentiation in mouse embryonic olfactory bulb (Vazquez et al, 2012). Vazquez and collogues also demonstrated that chemical inhibition of autophagy pathway will block the nervous system development in this animal (Vazquez et al, 2012).…”
Section: Autophagy and Stem Cellsmentioning
confidence: 97%
“…Different groups have demonstrated that ATG7 knock down in murine HSCs resulted in decelerated HSCs self-renewal and negatively affected myeloproliferation Mortensen et al, 2011). In contrast, upregulation of autophagy-genes has also been shown during neuronal differentiation in mouse embryonic olfactory bulb (Vazquez et al, 2012). Vazquez and collogues also demonstrated that chemical inhibition of autophagy pathway will block the nervous system development in this animal (Vazquez et al, 2012).…”
Section: Autophagy and Stem Cellsmentioning
confidence: 98%
See 1 more Smart Citation